From Passive Practice to Active Engagement: An Action Research on TOEIC Listening in EFL Higher Education - Mutiara Ayu; Dyah Aminatun (English Language Teaching Prima Journal (ELT), 2026)
This study investigates the effectiveness of classroom-based experimental strategies in enhancing student engagement and TOEIC listening performance in an EFL university context. Using an action research design, the study was conducted in two cycles involving 30 undergraduate students enrolled in a TOEIC preparation course. Data were collected through observation checklists, student questionnaires, reflective journals, and TOEIC listening tests. The findings revealed a substantial improvement in student engagement, with the average engagement score increasing from 61% in Cycle 1 to 79% in Cycle 2. All engagement dimensions showed growth, with emotional engagement demonstrating the highest increase. In terms of learning outcomes, students’ TOEIC listening scores improved significantly, with the mean score rising from 62 to 78. The proportion of students achieving scores ≥75 also increased from 30% to 70%. Statistical analysis using a paired sample t-test confirmed that the improvement was significant (t = 8.76, p < 0.001). These results indicate that shifting from passive listening practices to active, engagement-focused classroom experiments can effectively enhance both student engagement and listening performance.The study highlights the importance of interactive and reflective teaching practices in EFL higher education and suggests that action research can serve as a powerful tool for continuous instructional improvement.